A Preliminary Survey of Species Composition of Termites (Insecta: Isoptera) in Samunsam Wildlife Sanctuary, Sarawak - Norsyarizan Jamil; Wan Nurainie Wan Ismail; Siti Shamimi Abidin; Mazdan Ali Amaran; Ratnawati Hazali (Tropical Life Sciences Research, 2017)
A survey on termite species composition was conducted in Samunsam Wildlife Sanctuary, Sarawak in February, 2015. Overall 19 species of termite belonging to 13 genera and 8 subfamilies was found in the sanctuary. It was recorded the subfamily of Termitinae had the highest number of species (6 species, equal to 31.58% of total species), followed by Nasutermitinae (3 species, 15.79%), Macrotermitinae, Amitermitinae, Rhinotermitinae, Coptotermitinae, (2 species, 10.53% respectively), and Heterotermitinae, Termitogetoninae (1 species, 5.26% respectively). Since this rapid survey is the first termite assemblage representation in Samunsam Wildlife Sanctuary, the premilinary result may serve as the baseline data for termite composition in the area. Therefore, a whole coverage for the area within this sanctuary would definitely increase the number of termite species found in the sanctuary. Satu tinjauan mengenai komposisi spesies anai-anai telah dijalankan di Kawasan Perlindungan Hidupan Liar Samunsam, Sarawak pada bulan Februari 2015. Secara keseluruhannya, 19 spesies anai-anai daripada 13 genera dan 8 subfamili ditemui di kawasan perlindungan ini. Subfamili Termitinae direkodkan mempunyai bilangan spesies tertinggi (6 spesies, sama dengan 31.58% daripada jumlah spesies), diikuti oleh Nasutermitinae (3 spesies, 15.79%), Macrotermitinae, Amitermitinae, Rhinotermitinae, Coptotermitinae, (2 spesies, 10.53 % masing-masing), dan Heterotermitinae, Termitogetoninae (1 spesies, 5.26% masing-masing). Oleh kerana kajian pantas ini adalah mewakili pengumpulan awal anai-anai di Kawasan Perlindungan Hidupan Liar Samunsam, keputusan awal dapat berfungsi sebagai data dasar untuk komposisi anai-anai di kawasan tersebut. Oleh yang demikian, satu liputan menyeluruh untuk kawasan di dalam tempat perlindungan ini sudah pasti akan meningkatkan bilangan spesies anai-anai yang terdapat di kawasan perlindungan ini.